Physical activity instruction of older adults - Rose, Debra J. (Human Kinetics, 2019)
Physical Activity Instruction of Older Adults, Second Edition, is the most comprehensive text available for current and future fitness professionals who want to design and implement effective, safe, and fun physical activity programs for older adults with diverse functional capabilities. Along with an updated review of the research and literature, the second edition introduces a new chapter on the concept of whole-person wellness. It offers strategies for integrating the six dimensions of whole-person wellness (physical, emotional, intellectual, vocational, spiritual, and social) into health promotion and physical activity programs for older adults. This cohesive blend of theory, practical content, and detailed instruction is divided into four parts, each of which addresses one or more of the nine training modules that comprise International Curriculum Guidelines for Preparing Physical Activity Instructors of Older Adults, the expert-developed guidelines on which this text is based: Part I presents an overview of the physiological aspects of aging and the field of gerokinesiology to help readers understand the psychosocial and cognitive benefits derived from regular physical activity; Part II leads readers through the process of conducting preexercise health screenings and assessments, providing meaningful feedback to clients, evaluating program outcomes, and helping clients develop short- and long-term behavioral goals; Part III emphasizes programming principles and training methods that will facilitate the development of well-rounded and effective exercise programs. It includes specific activities for engaging older adults mentally, emotionally, socially, and spiritually along with myriad dynamic and static flexibility exercises to address joint and muscle flexibility, muscle strength, balance, mobility, endurance, and power; Part IV focuses on the teaching, motivation, communication, and leadership skills that are necessary for creating effective and safe programs for older adults, with or without specific medical conditions. The text also offers a variety of features devised to enhance reader understanding and learning retention. Chapters begin with a list of objectives to familiarize readers with the key concepts they will learn, and each chapter concludes with thought-provoking study questions and practical application activities to help readers use the information with real-world scenarios to prepare them to design well-rounded physical activity programs. Other student-friendly elements include chapter summaries and key terms. The content is supplemented with photos, figures, and tables, making the book interesting and visually appealing. Physical Activity Instruction of Older Adults, Second Edition, offers students and fitness professionals a contemporary approach that embraces a comprehensive wellness framework for designing health promotion and physical activity programs for older adults.